Creating climate change adaptation plans for rural coastal communities using Deliberation with Analysis as public participation for social learning. Issue 3 (May 2018) - Crawford, Pat; Beyea, Wayne; Bode, Claire; Doll, Julie; Menon, Rohit
Abstract : Public participation can foster social learning, creating environments where diverse groups can come together to dialogue about multifaceted societal and environmental issues and values. The case study uses Deliberation with Analysis, a process to integrate local residents' knowledge and values with local climate data, to create climate adaptation plans with two rural coastal Michigan communities. Iteration of the deliberative dialogue process is critical for allowing enough time for meaningful change and constructive communication to occur. Understanding where the community is starting from is important when tensions are high or deeply held values are challenged. Older techniques may need to be used to prepare the community for full participation in a deliberative process. Case highlights include the importance of community identity; potential negative impacts of climate change proposals on land-use rights; and the importance of multiple public engagement opportunities, or iterative learning loops, in climate-change plan development.